EDN1-AS, A Novel Long Non-coding RNA Regulating Endothelin-1 in Human Proximal Tubule Cells - Douma, Lauren G.; Solocinski, Kristen; Masten, Sarah H.; Barral, Dominique H.; Barilovits, Sarah J.; Jeffers, Lauren A.; Alder, Kareme D.; Patel, Ravi; Wingo, Charles S.; Brown, Kevin D.; Cain, Brian D.; Gumz, Michelle L. (Frontiers in Physiology, 2020)
Endothelin-1 (ET-1) is a peptide hormone that functions as a vasoconstrictor in the vasculature, whereas in the collecting duct of the kidney it exerts blood pressure-lowering effects via natriuretic actions. Aberrant ET-1 signaling is associated with several pathological states including hypertension and chronic kidney disease. ET-1 expression is regulated largely through transcriptional control of the gene that encodes ET-1, EDN1. Here we report a long, non-coding RNA (lncRNA) that appears to be antisense to the EDN1 gene, called EDN1-AS. Because EDN1-AS represents a potential novel mechanism to regulate ET-1 expression, we examined the regulation of EDN1-AS expression and action. A putative glucocorticoid receptor response (GR) element upstream of the predicted EDN1-AS transcription start site was identified using the ENCODE database and the UCSC genome browser. Two homozygous deletion clones of the element were generated using CRISPR/Cas9. This deletion resulted in a significant increase in the expression of EDN1-AS, which was associated with increased secretion of ET-1 peptide from HK-2 cells (2-fold increase in KO cells vs. CNTL, n=7, P<0.05). Phenotypic characterization of these CRISPR clones revealed a difference in cell growth rates. Using a standard growth assay, we determined that the KO1 clone exhibited a 3-fold increase in growth over 8 days compared to control cells (n=4, P<0.01) and the KO2 clone exhibited a 2-fold increase (n=4, P<0.01). These results support a role for EDN1-AS as a novel regulatory mechanism of ET-1 expression and cellular proliferation.